Population estimation of freshwater crocodiles (Crocodylus novaeguineae) and tree vegetation diversity at wildlife reserve of Mamberamo Foja, Papua, Indonesia - SUHARNO SUHARNO; AKHMAD KADIR; EDWARD SEMBIRING; ASKHARI DG. MASIKI; TAUFIK MUBARAK; LUSIANA D. RATNAWATI; NAFLI LESSIL; DANIAL IDRIS; JOHAN G. IMBENAI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suharno, Kadir A, Sembiring E, Masiki AD, Mubarak T, Lessil N, Ratnawati LD, Idris D, Imbenai JG. 2021. Population estimation of freshwater crocodiles (Crocodylus novaeguineae) and tree vegetation diversity at wildlife reserve of Mamberamo Foja, Papua, Indonesia. Biodiversitas 22: 2928-2936. The structure and composition of vegetation in the conservation area have a major influence on the existence of other flora and fauna, including freshwater crocodiles (C. novaeguineae). Wildlife Reserve of Mamberamo Foja (WRMF) is a conservation area in Papua that aims to protect the habitat and existence of freshwater crocodiles. The purpose of this study was to estimate the number of freshwater crocodile populations and tree species diversity in the WRMF, Papua. The method used was a field survey. The crocodile survey was carried out using the spotlight night count method. Tree species diversity was assessed using the line-transect plot method in 6 different locations representing the Upper, Central, and Lower Mamberamo. The results of the investigation showed that the freshwater crocodile population in the WRMF was around 0.3-19.7 individuals per kilometer. The population of this freshwater crocodile was very high, with an average of 4.5 individuals per 1-kilometer distance. The highest population numbers were found in the upstream Mamberamo River area 6.22 ind./km, followed by the central Mamberamo (2.21 ind./km) and downstream Mamberamo area (2.05 ind./km). Crocodiles were found in the Mamberamo River and other river systems, such as swamps and lakes. The tree vegetation in this area is still relatively good, and there are 112 species, dominated by the Moraceae, Burseraceae, Myrtaceae, Rubiaceae, Lauraceae, Dipterocarpaceae, and Euphorbiaceae families. The results of this study are important as a basis for determining the conservation policy for freshwater crocodiles that have limited distribution.